Experimental Study of Bottom Ash as an Admixture in M30 Concrete Mix (International Journal of Food and Nutritional Sciences, 2019)
To Reduce the usage of the Concrete content we are studying the different types of materialsstrength as an admixture and later if we are getting good results the studies will be forwardedto partial replacement and finally if possible the complete replacement of cement. This is thestudy with of the continuation of the Influence of thermal dust as an admixture with 0%,2%and 4% admixture and the continuation is carried forward. The experimental study of bottomash on normal strength concrete grade for 6% ,8% and 10% replacement cube were alsoprepared respectively.